Distribution pattern and ethnomedicinal uses of plants in Kanchanpur district, Far-Western Nepal - Bhatt, Man Dev; Kunwar, Ripu M (Ethnobotany Research and Applications, 2020)
Background: Far Western Region of Nepal boasts a large inventory of floral diversity including medicinal plants. In order to conserve medicinal plants in Nepal, it is necessary to better identify and assess their distribution, population, uses and interactions with culture. Medicinal plant species are main element in traditional system of healing in Nepal, which have been an integral part in history and cultural practices. In the present study, we aimed to document medicinal plant species and their indigenous uses in Bhimdatt-18, Far Western Nepal. It deals with the study of relationship of people with plants and the documentation of indigenous knowledge on how local plant resources are utilized by local people to cure different diseases. Methods: Fieldwork was carried out in two distinct sites for studying both distribution pattern and folk medicinal uses of plants. A total of ten quadrats in each site (N=20) were used to calculate phytosociological characteristics (frequency, density and Important Value Index). In order to assess the distribution of plant use knowledge, semi-structured questionnaire was used for interview and supplementary information was collected during informal group discussions. The use reports were categorized into medicinal and non-medicinal. Medicinal uses were further analyzed using the relative frequency citation (RFC). Results: We recorded 74 species of flowering plants at Bhimdatt-18, (Katan) Kanchanpur district, of which 35 species were recorded from agriculture farmlands (site 1) and the large number (66) from a conserved area (site 2). The recorded plants belonged to 29 families in which highest number of species was associated with families: Poaceae (16), Cyperaceae (12), Leguminosae (5), Asteraceae (4) and Malvaceae (4). On the basis of Importance Value Index, Imperata cylindrica (L.) Raeusch. (Poaceae), Ageratum conyzoides L. (Asteraceae), Desmodium triflorum (L.) DC. (Leguminosae) were placed as top three species, respectively. Of the recorded 74 species, 56 species of medicinal plant are used to cure different diseases through various modes of application. Conclusions: Dominant species, Centella asiatica (L.) Urban., Eclipta prostrata L. and Euphorbia hirta L. are popular medicinal plants, used in folklore of Kanchanpur district, Nepal. Of ten dominant plant species, nine are being used in ethnomedicine. Dominant plant species are frequently used in ethnomedicine in Kanchanpur district hinted that ecological and ethnobotanical accounts are interrelated. This study concluded that documentation and preservation of biodiversity and its associated knowledge is necessary which could generate further research activities and will help upcoming generations conserve ethnobotanical knowledge for the benefit of ecology and ethnobotany. Key words: Composition; Semi-structured interview; Importance Value Index; Use; Achyranthes aspera.